Higher Education in Portuguese Speaking African Countries - Vitorino Langa, Patrício (African Minds, 2014)
This publication is the result of a baseline study of the state of the higher education systems in the five Portuguese speaking countries in Africa (PALOP): Angola, Cape Verde, Guinea-Bissau, Mozambique and Sao Tome and Principe. The project was undertaken by an African international expert in the field of higher education studies and was fully sponsored and supported by the Association for the Development of Education in Africa (ADEA). The report offers a historical overview of the development of higher education in PALOP from colonial times to the present. The main objective of this baseline study is to map the landscape and dynamics of change in the higher education systems of PALOP countries. It focuses on describing the latest developments of trends of expansion, financing, governance and policy reforms closely linked to the development of higher education systems in these countries. Furthermore, the study will facilitate an informed debate and the dissemination of knowledge on the role of higher education for development in Africa.